Efektivitas Seduhan Daun Sirih terhadap Indeks Plak pada Anak Usia 12-15 tahun di Desa Pesisir Kabupaten Minahasa Tenggara - Jeanne d’arc Zafera Adam; Jean Hendry Raule; Vega Rosa Fiona; Jeana Lydia Maramis; Jeineke Ellen Ratuela; Anneke Tahulending; Oksfriani Jufri Sumampouw (Universitas Pahlawan Tuanku Tambusai, 2023)
Green betel leaves contain essential oils consisting of phenol and its derivatives, including betlephenol, estragol, kavikol, eugenol, and diastene enzymes. Betel leaf infusion is able to inhibit the growth of bacteria caused plaque. This study aims to determine the effectiveness of steeping betel leaves on plaque index in children aged 12-15 years old in coastal village of Southeast Regency. This is a quasi-experimental one group pre-post test research. The variable measured was dental hygiene using the Patient Hygiene Performance (PHP) plaque index. The treatment given to research subjects was giving steeping water and then gargled for 60 seconds. After that, the plaque index was measured. The data obtained were tabulated and presented in tabular form and tested using paired t-test. The results showed that the plaque index before gargling betel leaf stew was mostly in the bad criteria (60%). Furthermore, after gargling betel leaf decoction, the most plaque index was in the medium category (64%). The results of the paired-t test obtained a p value of 0.000 (p <0.05). This value indicates that there is a difference in the plaque index before and after being given treatment, which means that there is an effect of giving betel leaf infusion on the plaque index. It can be concluded that betel leaf infusion is effective in improving the plaque index in children aged 12-15 years old.